2008
DOI: 10.1001/jama.2008.717
|View full text |Cite|
|
Sign up to set email alerts
|

Inhaled Corticosteroids in Patients With Stable Chronic Obstructive Pulmonary Disease

Abstract: Context Recent studies of inhaled corticosteroid (ICS) therapy for managing stable chronic obstructive pulmonary disease (COPD) have yielded conflicting results regarding survival and risk of adverse events. Objective To systematically review and quantitatively synthesize the effects of ICS therapy on mortality and adverse events in patients with stable COPD. Data Sources Search of MEDLINE, CENTRAL, EMBASE, CINAHL, Web of Science, and PsychInfo through February 9, 2008. Study Selection Eligible studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
232
5
16

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(266 citation statements)
references
References 47 publications
13
232
5
16
Order By: Relevance
“…Although the use of inhaled corticosteroids in COPD patients has been demonstrated to be useful in the reduction of exacerbation events 16,17 and in protection against the development of complicated forms of hospitalized community-acquired pneumonia. 14,15 On the other hand, the long-term use of inhaled corticosteroids increases the risk of pneumonia, [18][19][20] especially with fluticasone. 20 Our study, performed in subjects with COPD exacerbation but without pneumonia, demonstrates that inhaled corticosteroids have no detrimental effect on the development of complications on admission or in other outcomes collected during the clinical course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of inhaled corticosteroids in COPD patients has been demonstrated to be useful in the reduction of exacerbation events 16,17 and in protection against the development of complicated forms of hospitalized community-acquired pneumonia. 14,15 On the other hand, the long-term use of inhaled corticosteroids increases the risk of pneumonia, [18][19][20] especially with fluticasone. 20 Our study, performed in subjects with COPD exacerbation but without pneumonia, demonstrates that inhaled corticosteroids have no detrimental effect on the development of complications on admission or in other outcomes collected during the clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Moreover, another large study followed stable COPD subjects for a period of 5 y and showed that the risk of severe pneumonia was strictly dose-related to exposure of inhaled corticosteroids and was higher in patients who had used fluticasone in comparison with budesonide. 20 We hypothesized that chronic domiciliary treatment with inhaled corticosteroids would influence the early systemic inflammatory response of COPD exacerbation and have an impact on clinical presentation and patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic accuracy of asthma and COPD diagnoses were tested using two differential diagnosis questionnaires. meta-analysis 14 concluded that the use of ICs in patients with stable COPD does not reduce mortality and significantly increases the incidence of pneumonia. Conversely, the use of long-acting beta agonists (LABAs) as monotherapy for asthma is not recommended for safety reasons.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these medications may increase the likelihood of infections: atypical antipsychotics may impair consciousness and increase the frequency of aspiration (Knol W & Al, 2008;Gau JT & Al, 2010); H2 blockers and protonic pump inhibitors (PPI) lead to decreased gastric acidity and may contribute to increased gastrointestinal infections (Laheij RI & Al;2004;Gulmez SE & Al, 2007;Eom CS & Al 2011;Laria A & Al, 2011). Oral and inhaled glucocorticoid therapy are associated with an increased dose-dependent risk of infections (Ernst P & Al, 2007;Calverley PM & Al, 2007;Kardos P & Al, 2007;Drummond MB & Al, 2008;Singh S & Al, 2009;Smitten AL, & Al 2008;Dixon WG & Al, 2011).…”
Section: Drugs Use In Elderly Nursing Homes Residentsmentioning
confidence: 99%